(untitled) (Palíndromo, 2023)
This essay results from the meetings of a study group called “Saturdays with Deleuze” and held from 2015 to 2019 at Universidade Federal de Santa Maria - RS/Brazil, aiming to problematize the conversations and the contamination triggered by the works studied in the encounter with artistic practices and research in education. Some images populate the text, giving expression to the experiments that took place in this regard during the study meetings. In a biographematic move (BARTHES, 2003), this work was produced by eight hands, that is by four singularities inhabited by polyphony that resonates and is signaled in this writing as: 1st, 2nd, 3rd, and 4th sets of hands. Each author wove his or her own writing and sent the text to the next pair of hands, exploring regions not yet imagined. The textual zones resulting from this writing-reading procedure (CORAZZA, 2008) intend to invite the reader to explore ways of seeing, reading, writing, living in the academy in interrelationship with art and philosophy as fields of creation.